2023
DOI: 10.1039/d2tc05444b
|View full text |Cite
|
Sign up to set email alerts
|

A photo-responsive organic electrochemical transistor

Abstract: The design of novel organic electrochemical transistor (OECT) channel materials that can be controlled by a whole range of external stimuli is key towards the emergence of unprecedented technologies in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The half‐life of the merocyanine of S2 in THF was relatively short (estimated t 1/2 ~3.6 mins. at 5 °C and 35 s at 20 °C; Figure S23 and S24), which is typical for merocyanines in low‐polarity solvents [69] . Control experiments indicated that irradiation of the o ‐fluorinated azobenzene S1 at this wavelength (300 nm) does not result in any appreciable degree of isomerization (Figure S19 and S20).…”
Section: Figurementioning
confidence: 82%
See 1 more Smart Citation
“…The half‐life of the merocyanine of S2 in THF was relatively short (estimated t 1/2 ~3.6 mins. at 5 °C and 35 s at 20 °C; Figure S23 and S24), which is typical for merocyanines in low‐polarity solvents [69] . Control experiments indicated that irradiation of the o ‐fluorinated azobenzene S1 at this wavelength (300 nm) does not result in any appreciable degree of isomerization (Figure S19 and S20).…”
Section: Figurementioning
confidence: 82%
“…at 5 °C and 35 s at 20 °C; Figure S23 and S24), which is typical for merocyanines in low-polarity solvents. [69] Control experiments indicated that irradiation of the o-fluorinated azobenzene S1 at this wavelength (300 nm) does not result in any appreciable degree of isomerization (Figure S19 and S20). Hence, the wavelength-selectivity in this dyad stems not only from band separation (Figure S26) but also due to significant differences in the efficiency of the photoisomerization at the selected wavelengths.…”
mentioning
confidence: 97%
“…The most recent work (2023) demonstrated photo-responsive OECTs created via pre-patterned Au electrodes and drop-cast solutions of pgBTTT blended with other materials, also dissolved in chloroform. [31] This study reports on the combination of printing technologies to create all-printed accumulation mode OECTs. The ptype semiconducting conjugated polymer pgBTTT was inkjet printed to create the OECT channels, while the remaining layers were screen printed to complete the vertically stacked OECT devices.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent work (2023) demonstrated photo‐responsive OECTs created via pre‐patterned Au electrodes and drop‐cast solutions of pgBTTT blended with other materials, also dissolved in chloroform. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%